2013
DOI: 10.1186/1756-0500-6-292
|View full text |Cite
|
Sign up to set email alerts
|

Associated risk factors of urinary tract infection among pregnant women at Felege Hiwot Referral Hospital, Bahir Dar, North West Ethiopia

Abstract: BackgroundUrinary tract infections (UTIs) are among the most common bacterial infections in humans, both in the community and hospital settings. It is a serious health problem affecting millions of people each year and is the leading cause of Gram-negative bacteremia. We previously conducted a study on “Urinary Bacterial Profile and Antibiotic Susceptibility Pattern of UTI among Pregnant Women in North West Ethiopia” but the study did not address risk factors associated with urinary tract infection so the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
93
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 11 publications
20
93
5
5
Order By: Relevance
“…AlJawadi (2012) [50] also reported short child spacing (<2 years) was seen among less than half of the pregnant women with UTI.Regarding maternal anemia, this study results revealed that Hemoglobin level < 11 mg/dl was significantly associated with UTI during pregnancy. Similar results were reported by Haider et al, 2010 [46] in Pakistan and Emiru et al, 2013 [48] in Ethiopia who studied UTI among pregnant women. Also this study results agrees with studies of asymptomatic bacteruria among pregnant women by Sescon et al (2003) [51] in Philippines, Enayat et al (2007) [52] in Iran and Taher et al, (2009) [53] in Qatar.…”
Section: Prevalence and Risk Factors Of Urinary Tract Infection Amongsupporting
confidence: 80%
See 1 more Smart Citation
“…AlJawadi (2012) [50] also reported short child spacing (<2 years) was seen among less than half of the pregnant women with UTI.Regarding maternal anemia, this study results revealed that Hemoglobin level < 11 mg/dl was significantly associated with UTI during pregnancy. Similar results were reported by Haider et al, 2010 [46] in Pakistan and Emiru et al, 2013 [48] in Ethiopia who studied UTI among pregnant women. Also this study results agrees with studies of asymptomatic bacteruria among pregnant women by Sescon et al (2003) [51] in Philippines, Enayat et al (2007) [52] in Iran and Taher et al, (2009) [53] in Qatar.…”
Section: Prevalence and Risk Factors Of Urinary Tract Infection Amongsupporting
confidence: 80%
“…Similarly Onuoha and Fatokun (2014) [21] reported that multiparity has an increased risk factor of developing bacteruria among pregnant women. While Emiru et al (2013) [48] found that UTI is more common in primigravida. Dimetry et al (2007) [11] also, reported discordant findings regarding association of increased UTI with multigravidas, gestational age, and those who have more than one child relating the results to the age, recurrent exposure to stasis of urine, or former infections history.…”
Section: Prevalence and Risk Factors Of Urinary Tract Infection Amongmentioning
confidence: 99%
“…[21] The variation might be justified by the reality that differences exist in geographical location, social behavior of the population, the environment, the model of educational status, and study settings (primary care, community-based, or in hospitals). The finding of our study is higher than the studies done in Northwest Ethiopia (8.5%), [22] Central Ethiopia (Addis Ababa) (10.6%), [23] Tanzania (4.1%), [24] and Eritrea (10.5%). [25] The possible explanation for this disparity might be related to variations in the study population, time of study period and sample size of study participants.…”
Section: Discussioncontrasting
confidence: 56%
“…The significance of risk factors like anaemia, low income level, past history of UTI and sexual activity in causing UTI among women during pregnancy has been explored and validated by several researchers. 33 Presence of 100000 organisms per ml of urine sample in addition to the presence of an exceeding number of white blood cells can signify the occurrence of UTI. The count of >5 white blood cells in a symptomatic patient is considered to be significant.…”
Section: Uti During Pregnancymentioning
confidence: 99%